Prevalence and Atypical Clinical Characteristics of NOTCH3 Mutations Among Patients Admitted for Acute Lacunar Infarctions - Okada, Takashi; Washida, Kazuo; Irie, Kenichi; Saito, Satoshi; Noguchi, Michio; Tomita, Tsutomu; Koga, Masatoshi; Toyoda, Kazunori; Okazaki, Shuhei; Koizumi, Takashi; Mizuta, Ikuko; Mizuno, Toshiki; et al. (Frontiers in Aging Neuroscience, 2020)
Objectives Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is the most common hereditary small vessel disease, with reported frequencies of 2-5/100,000 individuals. Recently, it has been reported that some patients with NOTCH3 gene mutations show atypical clinical symptoms of CADASIL. Assuming that CADASIL is underdiagnosed in some cases of lacunar infarction, this study was designed to examine the prevalence of NOTCH3 gene mutations in the patients at highest risk who were admitted for lacunar infarctions. Methods From January 2011 to April 2018, 1,094 patients with lacunar infarctions were admitted to our hospital, of whom 31 patients without hypertension but with white matter disease (Fazekas scale 2 or 3) were selected and genetically analyzed for NOTCH3 gene mutations (Phase 1). Furthermore, 54 patients, who were 60 years or younger, were analyzed for NOTCH3 mutations (Phase 2). NOTCH3 exons 2–24, which encode the epidermal growth factor-like repeat domain of the NOTCH3 receptor, were analyzed for mutations by direct sequencing of genomic DNA. Results Three patients presented NOTCH3 p.R75P mutations: two in the Phase 1 and one in the Phase 2 cohort. Among patients aged 60 years or younger and those without hypertension but with moderate-to-severe white matter lesions, the carrier frequency of p.R75P was 3.5% (3/85), which was significantly higher than that in the Japanese general population (4.7KJPN) (odds ratio [95% CI]=58.2 [11.6–292.5]). All three patients with NOTCH3 mutations had family histories of stroke, and the average patient age was 51.3 years. All three patients also showed white matter lesions in the external capsule but not in the temporal pole. The CADASIL and CADASIL scale-J scores of the three patients were 6, 17, 7 (mean,10.0) and 13, 20, 10 (mean,14.3), respectively. Conclusion: Among patients hospitalized for lacunar infarctions, the p.R75P prevalence may be higher than previously estimated. The NOTCH3 p.R75P mutation may be underdiagnosed in patients with early-onset lacunar infarctions due to the atypical clinical and neuroimaging features of CADASIL. Early-onset, presence of family history of stroke, external capsule lesions, and absence of hypertension may help predict underlying NOTCH3 mutations despite no temporal white matter lesions.